Effect of CHO loading patterns on running performance - Chen, Y.; Wong, S. H. S.; Xu, X.; Hao, X.; Wong, C. K.; Lam, C. W. (International Journal of Sports Medicine, 2008)
This study examined the influence of 3-day isoenergetic carbohydrate (CHO) loading with different glycemic index (GI) and glycemic load (GL) meals on running performance and metabolic responses. With a randomized crossover design, nine male runners performed a 1-h run at 70 % V·O2max followed by a 10-km performance run after a 3-day diet adaptation, which involved different GI and GL meals [CHO intake (%), GI, and GL per day were 73 %, 80, and 553 for the high GI and high GL (HH); 73 %, 36, and 249 for the low GI and low GL (LL); and 31 %, 79, and 227 for the high GI and low GL (HL), respectively]. There were no differences in the time to complete the 10-km run between the two high-CHO trials; however, the performance in the LL trial was improved as compared to that in the HL trial (mean ± SEM: HH vs. LL vs. HL: 51.3 ± 5.3 vs. 48.6 ± 1.3 vs. 55.3 ± 6.9 min). It appears that the amount, rather than the nature, of the CHO consumed during the 3-day isoenergetic CHO loading may be the most overriding factor on subsequent metabolism and endurance run performance.